Implementation of the 7P Marketing Mix at Manyi Bali Café in Nusa Dua - Dewi, Kadek Budhistina; Widuri, Setyowati Ayu; Juniari, Ni Kadek Eni (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the application of the 7P marketing mix to Manyi Bali in Nusa Dua. The data analysis technique of this research is descriptive quantitative. This technique is used to explain the implementation of the 7P marketing mix at Manyi Bali Café. Overall, the implementation of the 7P marketing mix at Manyi Bali Café got an average value of 3.97 in the agreed interval class. This indicates that Manyi Bali Café has implemented the 7P marketing mix well to continue to develop its business well and can provide the best for all consumers. However, there is still one indicator that has not gotten the maximum value, namely the price, which is in the less agreeable interval class. This indicates that there are still some respondents who disagree with statement that the price offered is affordable and the price is in accordance with the quality of the product. Overall, the implementation of the 7P marketing mix at Manyi Bali Café got an average value of 3.97 which was in the agreed interval class. This shows that the application is in a good category. A good and well-calculated marketing concept will of course have a positive impact on the development of the business being undertaken.